Seed product requirements of the potato-processing industry in Eastern Africa : Implications for CGIAR market segmentation and target product profiles - Naziri, Diego; Devaux, André; Wauters, P.; Mendes, Thiago; Lindqvist-Kreuze, Hannele; Hareau, Guy (CGIAR, 2024)
The current CGIAR seed product market segmentation includes one segment related to potato-processing varieties in Eastern Africa, for which the target product profile (TPP), i.e., the blueprint for the ideal product, has been co-developed by breeders from the International Potato Center (CIP) and partners. The processing industry in the region is expanding rapidly. While firms largely procure tubers of varieties not specifically bred for processing, there is growing evidence that, as the sector develops, they will progressively set and enforce stricter requirements for raw material. In this study, we investigated the requirements of processing companies in the region, with a focus on Kenya, Rwanda, and Uganda. We also discuss the alignment of the industry’s requirements with the breeding efforts by CIP and national programs as defined in the corresponding TPP. We found that the current segmentation for potato in Eastern Africa can be refined to better reflect the industry’s requirements, especially related to different end products (chips and crisps). The findings provide additional insights on how the existing TPP for the processing segment can be adjusted to make breeding more market oriented and responsive to end-user preferences. While it is expected that this will contribute to higher and faster variety uptake and adoption, the challenge ahead for breeders will be to strike the right balance between farmers’ and processors’ requirements.